Microsoft Exchange Server 2007 : - Stanek, William R. (Microsoft Press, 2007)
Here's the practical, pocket-sized reference for IT professionals who administer and support Microsoft Exchange Server 2007. This unique guide provides essential details for using this next-generation messaging and collaboration platform to deliver better performance, interoperability, and end-user experience. Written by an award-winning author of more than two dozen computer books, this guide puts expert installation, migration, administration, and troubleshooting advice right at your fingertips.